SIMBOL, METAFORA, ALUSI, DAN PARALELISME DALAM NOVEL FRANKENSTEIN KARYA MARY SHELLEY - Andhini Aulia Pratiwi; Fathimah Az Zahro; Rizal Nazarudin Firdaus; Nurholis Nurholis (Cahaya Ilmu Bangsa Institute, 2024)
Abstract This article examines the analysis of symbols, metaphors, allusions, and parallelism in Mary Shelley’s novel Frankenstein, a Gothic tale depicting the ambition of a young scientist, Victor Frankenstein, to create life through scientific experimentation. The novel not only explores themes of scientific ethics and the consequences of human actions but also delves into fear, loneliness, and the impact of neglecting responsibility toward creation. This study provides insights into narrative style, Gothic elements, and the novel’s modern relevance, especially regarding technological ethics issues such as artificial intelligence and genetic engineering. Keywords: symbols, metaphors, allusions, parallelism, scientific ethics, Frankenstein. Abstrak Artikel ini membahas analisis simbol, metafora, alusi, dan paralelisme dalam novel Frankenstein karya Mary Shelley, sebuah cerita gotik yang menggambarkan ambisi ilmuwan muda, Victor Frankenstein, dalam menciptakan kehidupan melalui eksperimen ilmiah. Novel ini tidak hanya mengangkat tema-tema etika ilmiah dan konsekuensi dari tindakan manusia, tetapi juga menggambarkan ketakutan, kesepian, serta dampak dari kurangnya tanggung jawab terhadap ciptaan. Kajian ini memberikan wawasan tentang gaya naratif, unsur gotik, serta relevansi novel dalam konteks modern, khususnya terkait isu etika teknologi seperti kecerdasan buatan dan rekayasa genetik. Kata Kunci: simbol, metafora, alusi, paralelisme, etika ilmiah, Frankenstein